Is botulinum toxin a cause or a cure for headaches? - KAPTANOĞLU, ASLI FERİDE (WILEY, 2022)
Background Botulinum toxin is used in the treatment of headache as well as cosmetic indications. In recent years, headache cases have been encountered after botulinum toxin injections for cosmetic purposes. However, no clinical studies have been conducted on this seemingly paradoxical issue. Objective In our study, the aim was to evaluate the frequency of occurrence of headache and its clinical features in patients who had undergone botulinum toxin application for cosmetic purposes. Methods A total of 186 patients who were treated with onabotulinum toxin A for cosmetic purposes in our clinic between January 2019 and January 2021 were retrospectively screened, and the clinical and demographic characteristics of the patients who reported headache complaints were examined. Results Headache was reported in 19 (10.2%) of the 186 patients included in the study. Of the 19 patients who reported headaches, 17 (89.4%) had the onset of the complaint within the first 24 h, the complaint was resolved within the first 3 days in 16 (84.2%), and 12 (63.1%) reported spontaneous regression without the need for painkillers. The rate of development of headache complaints after the procedure was found to be statistically significantly higher in patients diagnosed with hypertension (p = 0.000) and patients treated for bunny line (p = 0.016). Ten patients (52.6%) described constant, 17 patients (89.5%) had diffuse, and 11 patients (57.9%) had throbbing-type headaches. Conclusion Botulinum toxin application causes diffuse, constant, throbbing-type headaches that start in the early period and ends within a short time without the need for treatment.
Keywords: botulinum toxin; facial; headache; pain; wrinkles; INJECTION